ANALISIS BIOEKONOMI IKAN PELAGIS PADA USAHA PERIKANAN TANGKAP DI PELABUHAN PERIKANAN PANTAI TAWANG KABUPATEN KENDAL - Rahman, Dhiya Rifqi; Triarso, Imam; -, Asriyanto (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Kendal Regency Seawaters is one of distribution area of potential pelagical fish. If there is no control in the resources utilization, the resources will be threaten. This research aims were to analyze biological and economic aspect of the utilization of the pelagic fish in Tawang fishing port Kendal Regency Seawaters which includes Catch per Unit Effort (CPUE), Maximum Sustainable Yield (MSY), Maximum Economic Yield (MEY), and Open Access Equilibrium (OAE). This research conducted in March-April 2012. Research material was unit of fishing industries was put pelagical fish target in Tawang fishing port. Research method was case study descriptive method. Sampling method was purposive sampling with 30 samples obtained. Data analysis method used time series and bioeconomic method – Gordon-Schaefer Model. This study showed that the average of Catch per Unit Effort (CPUE) pelagical fish potency rate for 2007-2011 in Tawang fishing port Kendal Regency Seawaters is 0, 417 tonnes/trip. The optimum product (Copt) of the Maximum Sustainable Yield (MSY) was 307,168 tonnes per year with optimum effort (Eopt) was 490 trip per year. The optimum product (Copt) of the Maximum Economic Yield (MEY) was 307,008 tonnes per year with optimum effort (Eopt) was 479 trip per year. The optimum product (Copt) of the Open Access Equilibrium (OAE) was 27,342 tonnes per year with optimum effort (Eopt) was 958 trip per year. The pelagical fish resource utilization rate during the last 5 years in Tawang fishing port Kendal Regency has an average rating of 85,57%.